Openings As an Important Aspect of Traditional Market Design Font - Vieka Thinsie Houward; Firman Eddy (Talenta Publisher, 2023)
Traditional markets are known as one of the pillars of people’s economic state, and because of that, they need to be developed properly. Despite that, traditional markets nowadays have a negative stigma which is dirty and smelly. To increase the interest of residents, many factors can be used such as adjusting and improving traditional market facilities. Design elements can help in solving this problem by adding openings and adjusting market structure modules. This paper aims to provide more information about the effect of market openings and modules on air circulation (odor) in the market. The method used in this research is a literature study, namely by collecting data related to solutions to counteract the smelly market through articles, journals, and books. The existence of an opening is to provide natural air circulation into a room, also the sunlight helps eradicate bacteria inside the humid room. The arrangement of the modules is also important so the odor of each segment does not mix. The existence of traditional markets must be maintained and developed so that it is necessary to overcome the bad smell in the current market because it can affect and have an impact on the interest of visitors to come to traditional markets.